A General Equilibrium Approach to Marxian Economics - Roemer, John E. (Econometrica, 1980)
In the first part of the paper, a model is proposed which places the Marxian and Sraffian conceptions of a capitalist economy in a general equilibrium framework. A central concern of these writers is that the economy be reproducible; this is incorporated formally into the equilibrium definition. Capitalists maximize profits subject to a capital constraint and workers are paid a subsistence wage. Equilibrium existence theorems are proved. In the second part, the welfare properties of the equilibria are examined-which, in the Marxian tradition, involve the notion of exploitation. It is shown that the possibility of exploitation is necessary and sufficient for all equilibria to sustain positive profits, if a certain technological condition holds. Finally, the notion of a subsistence bundle is dispensed with, and a Marxian determination of workers' consumption is proposed. In addition to placing the formal Marxian model into a general equilibrium context, the specification of production here is more general than the usual Leontief or von Neumann technologies: production sets are assumed to be only convex.